Influence of Micronutrients on the Food Consumption Rate and Silk Production of Bombyx mori (Lepidoptera: Bombycidae) Reared on Mulberry Plants Grown in a Mountainous Agro-Ecological Condition - Ruth, Lalfelpuii; Ghatak, Souvik; Subbarayan, Sarathbabu; Choudhury, Bidyut Nath; Gurusubramanian, Guruswami; Kumar, Nachimuthu Senthil; Bin, Tang (Frontiers in Physiology, 2019)
The study involves analyzing the performance of bivoltine Bombyx mori larvae reared on different host plants varieties. The consumption rate of different strains of B. mori was high when fed with Jorhat and TR10 mulberry plant varieties. Jorhat and TR10 mulberry plant varieties were found to contain significant amount of calcium, potassium, magnesium and phosphorus. Local (Hmute) mulberry plant variety had high amount of protein, carbohydrate and reducing sugar. Majority of the B. mori strains reared on Jorhat and TR10 mulberry plant varieties had high level of fibroin protein which resulted in increased silk productivity than those larvae reared with other mulberry varieties. The filament length was higher when reared on Jorhat and TR10 mulberry plant varieties. CSR4 x CSR2, FC1 x FC2 and FC2 x FC1 strains reared on Jorhat and TR10 mulberry plant varieties performed well interms of economic parameters. Proteins and other nutrients in combination with high levels of micronutrients are very much essential for better silk quality. The present study attempted to identify the most suitable host plants for silkworm rearing under mountainous agro-ecological conditions which can lead to sustainable production of silk in relation to physiological and economic parameters.